Commerce Register Analysis of Minangkabau Vernacular in a Colloquial Conversation: A Sociolinguistics Studies - Nurani, Siti; Widya, Widya; Harared, Nico (UICELL, 2017)
This research aims at identifying register used in the commerce colloquial conversations among sellers and buyers. Systemic Functional Linguistics (SFL) approach is applied to examine the linguistic features viewed from the aspect of field, tenor and mode of discourse. Findings show that in the field of discourse, registers release the experiential domain of nouns, verbs, idiomatic expression, and word blending. The goal orientation appears to have both short and long term while the social activity results in exchanges among participants. Furthermore, in the field of tenor, participants have an equal agentive role as they have same social function. The social role is non-hierarchic and the social distance is minimal. Finally, in the mode of discourse, both constitutive and ancillary language role formed in present simple, past simple and future simple. The channel is phonic and the medium is spoken with visual contact as it is characterized by the use of back channel signs. The Systemic Functional Linguistics approach employed in this research could be used as the parameter for educators in teaching Sociolinguistics especially in conducting discourse analysis in various colloquial discourse contexts.